The Role of NGOs (non-governmental organizations) in participatory prevention of environmental crimes - Aghajani, Shirin (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Crimes against the environment are actions that in certain circumstances cause Pollution, destruction or damage to the environment. The importance of preventing these crimes is because it relates directly to the health of human beings. Today non-governmental actors play an important role in the national and international arena. The Geographical diversity of activities and their different functions has led to state actors cannot be indifferent to the role of these new actors. NGOs are involved in two "competing" or "partner" forms of governments. In issues related to human rights, these to be a competitor to governments. While in the case of issues such as health development and environment it is considered as a partner of governments. In Iran's legal system the action role of these organizations in regard to environmental protection is undeniable: But there is still a lot of vacuum at the reactionary stage: must provide suitable substrates for the active Participation of this actors in environmental litigation: In a way that they can achieve a favorable position in criminal proceedings: Also, the organization of NGOS as the right hand of governments in helping to solve these problems has also a special place. The research method was descriptive-analytic and the date was collected as a library. In this research we decided to investigate the role of grassroots institutions in preventing environmental crime and accomplish the strengths and weaknesses of these institutions.